Long-Term Complications and Patient-Reported Outcomes After Alloplastic Breast Reconstruction. (March 2022) - Lee, Chia-Chun; Perng, Cherng-Kang; Ma, Hsu; Wu, Szu-Hsien; Hsiao, Fu-Yin; Tseng, Ling-Ming; Tsai, Yi-Fang; Lin, Yen-Shu; Lien, Pei-Ju; Feng, Chin-Jung
Abstract : Background: The most widely used method for breast reconstruction in Taiwan is alloplastic breast reconstruction, and traditionally, it can be categorized into immediate or delayed, single-stage or 2-stage procedures. We evaluated clinical outcomes and analyzed patients' self-reported satisfaction and quality of life after alloplastic breast reconstruction based on a previous preliminary study. Patient and Methods: The patients who underwent primary alloplastic breast reconstruction after mastectomy were recruited in 2006 to 2020 at a single institute in Taiwan. The assessment of clinical outcomes was conducted by retrospective chart review and risk analysis. The patients also completed the BREAST-Q, a condition-specific patient-reported outcome measure, at least 6 months after treatment. Results: A total of 237 patients with 247 reconstructed breasts were enrolled in this study. The demographics showed that 205 (83%) were reconstructed using a 2-stage tissue expander-based procedure and 42 (17%) were 1-stage direct-to-implant reconstructions. The mean follow-up time was 79.5 months. The clinical assessment revealed that the overall complication rate was 34%, with infection being the most common (21 patients; 8%). According to risk analysis, smoking (odds ratio, 7.626; 95% confidence interval, 1.56–37.30; P = 0.012), and nipple-sparing mastectomy (odds ratio, 3.281; 95% confidence interval, 1.54–6.99; P = 0.002) were significant risk factors for overall complications. The questionnaire response rate was 38% (94 of 247), at least 6 months after treatment. The total mean score was 69.78. Conclusions: At a single institute in Taiwan from 2006 to 2020, alloplastic breast reconstruction, either single- or 2-stage, have acceptable complication rate and good postoperative satisfaction based on patient-reported outcomes. Both patient- and surgery-related factors presented as significant risk factors. Precise patient selection and comprehensive discussion between the patient and physician may play the important role to achieve optimal aesthetic outcomes.